2015
DOI: 10.1016/j.hal.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton community grazing impact on a toxic bloom of Alexandrium fundyense in the Nauset Marsh System, Cape Cod, Massachusetts, USA

Abstract: Embayments and salt ponds along the coast of Massachusetts can host localized blooms of the toxic dinoflagellate Alexandrium fundyense. One such system, exhibiting a long history of toxicity and annual closures of shellfish beds, is the Nauset Marsh System (NMS) on Cape Cod. In order measure net growth rates of natural A. fundyense populations in the NMS during spring 2012, incubation experiments were conducted on seawater samples from two salt ponds within the NMS (Salt Pond and Mill Pond). Seawater samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Assuming all of these transformed to new cysts, average deposition on the pond's bottom would be approximately 15,000 cysts cm 2 , comparable to the cyst deposition observed after the Salt Pond bloom in 2013, a year when peak cell concentrations again were > 10 6 cells L −1 (Brosnahan, Fischer, and Anderson unpubl.). Because the bloom's rate of decline during its zygotic phase (−1.0 d −1 ) far exceeded estimates of overall losses due to grazing and parasitism (approximately −0.3 d −1 ; Petitpas et al ), encystment was likely the dominant factor leading to bloom termination. We are unable to confirm this conclusion, however, because no comparable time series of cyst abundance during the 2012 bloom exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming all of these transformed to new cysts, average deposition on the pond's bottom would be approximately 15,000 cysts cm 2 , comparable to the cyst deposition observed after the Salt Pond bloom in 2013, a year when peak cell concentrations again were > 10 6 cells L −1 (Brosnahan, Fischer, and Anderson unpubl.). Because the bloom's rate of decline during its zygotic phase (−1.0 d −1 ) far exceeded estimates of overall losses due to grazing and parasitism (approximately −0.3 d −1 ; Petitpas et al ), encystment was likely the dominant factor leading to bloom termination. We are unable to confirm this conclusion, however, because no comparable time series of cyst abundance during the 2012 bloom exists.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to the third challenge was made possible through the development of a cable-free raft that supported the IFCB deployment at Salt Pond, a site that retains A. fundyense blooms and can be adequately characterized by sampling at a single location and depth. Deployment at Salt Pond also enabled comparison to weekly surveys of A. fundyense that were ongoing through other parallel projects within the NMS (Velo-Su arez et al 2013;Ralston et al 2014Ralston et al , 2015Petitpas et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily loss rates are estimated to alternate between approximately 0.1 d -1 and 0.3 d -1 during neap and spring tide cycles, respectively, and there is interannual variability depending on the stratification and swimming behavior . Specific loss rates due to grazing are unknown but their impact has not been shown to be a major factor in bloom development or decline (Petitpas et al 2015;. Unlike the model of , this study's model begins many months earlier in the year when loss rates have not been estimated.…”
Section: Loss Ratementioning
confidence: 99%
“…Finally, perhaps the greatest uncertainty is the lack of understanding of grazing rates and the environmental factors or population dynamics that control them (Petitpas et al 2015). The work of demonstrated that the net accumulation rates during the bloom were similar to the upper limit of laboratory growth rates of A. catenella.…”
Section: Low Loss Rates In Salt Pondmentioning
confidence: 99%